Absolute configuration of trixanolides from Trixis pallida - Kotowicz, Claudia (2001)
The aerial parts of Trixis pallida afforded seven known trixanolides (18-24) together with 17 new trixanolides (1-17). Their structures were determined by 1D and 2D NMR techniques, while the absolute configuration of the trixane skeleton was determined using the Mosher method and turned out to be enantiomeric to that reported using the Horeau method. This result is further discussed from the biosynthetic point of view.